Amiodarone and Parkinsonism: a pharmacovigilance study. (9th November 2020) - Montastruc, Jean‐Louis; Durrieu, Geneviève
Abstract: Background: Some case reports have described parkinsonism with amiodarone. We investigated a putative association between parkinsonism and exposure to amiodarone. Methods: We used the WHO pharmacovigilance database (VigiBase ® ). All adverse drug reactions with 'Parkinson‐like events' and amiodarone were included. Four disproportionality analyses were performed: 1/after inclusion of all reports, 2/according to sex, 3/for the twenty last years (2000–2019), and 4/after exclusion of concomitant drugs known to induce parkinsonism (antipsychotic, antivertigo, antiemetic antinauseant drugs, flunarizine). Results are expressed as reporting odds ratios (ROR; 95% CI) and information component (IC). Results: No significant association was found in the whole population [ROR = 0.83 (0.65–1.06), IC = −0.7 (IC025  = −0.65)], in men, in women, for the 2000–2019 years, or after exclusion of drugs inducing parkinsonism. Conclusion: We failed to find any signal of parkinsonism with amiodarone. We suggest that reports of parkinsonism with amiodarone could be mainly explained by other underlying causes.